Nanostructured N doped TiO2 efficient stable catalyst for Kabachnik–Fields reaction under microwave irradiation. Issue 45 (20th July 2020) - Kunde, Sachin P.; Kanade, Kaluram G.; Karale, Bhausaheb K.; Akolkar, Hemant N.; Arbuj, Sudhir S.; Randhavane, Pratibha V.; Shinde, Santosh T.; Shaikh, Mubarak H.; Kulkarni, Aniruddha K.
Abstract : Herein, we report nitrogen-doped TiO2 (N-TiO2 ) solid-acid nanocatalysts with heterogeneous structure employed for the solvent-free synthesis of α-aminophosphonates through Kabachnik–Fields reaction. Abstract : Herein, we report nitrogen-doped TiO2 (N-TiO2 ) solid-acid nanocatalysts with heterogeneous structure employed for the solvent-free synthesis of α-aminophosphonates through Kabachnik–Fields reaction. N-TiO2 were synthesized by direct amination using triethylamine as a source of nitrogen at low temperature and optimized by varying the volume ratios of TiCl4, methanol, water, and triethylamine, under identical conditions. An X-ray diffraction (XRD) study showed the formation of a rutile phase and the crystalline size is 10 nm. The nanostructural features of N-TiO2 were examined by HR-TEM analysis, which showed they had rod-like morphology with a diameter of ∼7 to 10 nm. Diffuse reflectance spectra show the extended absorbance in the visible region with a narrowing in the band gap of 2.85 eV, and the high resolution XPS spectrum of the N 1s region confirmed successful doping of N in the TiO2 lattice. More significantly, we found that as-synthesized N-TiO2 showed significantly higher catalytic activity than commercially available TiO2 for the synthesis of a novel series of α-amino phosphonates via Kabachnik–Fields reaction under microwave irradiation conditions. The improved catalytic activity is due to the presence of strong and Bronsted acid sites on a porous nanorod surface. This work signifies N-TiO2 is an efficient stable catalyst for the synthesis of α-aminophosphonate derivatives.